MO014: Development and Validation of the Thirst Distress Scale for Patients with Autosomal Dominant Polycystic Kidney Disease. (3rd May 2022) - Gül Özcan, Şeyda; Bek, Sibel; Eren, Necmi; Atli, Zeynep; Yıldız, Abdülmecit; Kocyigit, Ismail; Cavdar, Caner; Seyahi, Nurhan; Ecder, Tevfik; Waldreus, Nana
Abstract: BACKGROUND AND AIMS: Abundant water intake is advised for patients with autosomal dominant polycystic kidney disease (ADPKD) Meijer and Casteleijn (Riding the waves: evidence for a beneficial effect of increased water intake in autosomal dominant polycystic kidney disease patients? Nephrol Dialysis Transpl . 2014;29 (9):1615–1617). Thirst, which can be defined as a sensation of dryness in the mouth and throat associated with a desire for liquids, is the main driver for fluid consumption Fitzsimons (Thirst. Physiol Rev 1972;52 (2):468–561). However, daily routines may limit water intake. There is no established tool to quantify the drivers of water intake in ADPKD patients. In this study, it was aimed to develop and validate a thirst distress scale (TDS) to quantify the factors of water intake in ADPKD patients. METHOD: The TDS-heart failure questionnaire was first (i) translated to Turkish using the approach recommended by the guidelines of the World Health Organization and finally (ii) modified to adapt to patients with ADPKD with totally 12 questions assessing (a) what may affect water intake, (b) what limit water intake and (c) what disturbing effects thirst may have on quality of life. The guidelines of the World Health Organization were used to translate the questionnaire to Turkish. An electronic survey with SurveyMonkey platform was used to collect data on thirst with TDS-PKD and thirst intensity (visual analog scale, VAS). Internal consistency of the TDS-PKD was evaluated with Cronbach's alpha. Exploratory factor analysis was conducted to reveal the validity and the factor structure of the questions in the questionnaire. RESULTS: The questionnaire was filled in by 154 ADPKD patients, of which 116 were on tolvaptan therapy. The time taken to answer the questions was about 4 min. The TDS-PKD questionnaire showed good internal consistency with a Cronbach's alpha value of 0.867. According to the exploratory factor analysis, a three-factor structure was obtained, meaning that there are three constructs about thirst in the TDS-PKD. Three factors explained 62.57% of the total variance. Factor one consisted of questions 1–7, factor two 8–10 and factor three 11–12. All three factors were significantly associated with thirst intensity ( r = 0.505, r = 0.244 and r = 197, respectively). The average score of TDS-PDK was 40.2 ± 10.5, and the average VAS score was 8.5 ± 0.7. CONCLUSION: The TDS-PKD questionnaire is a valid and reliable tool for evaluating the thirst distress in ADPKD patients.